An Algorithm for Managing Syndromic Craniosynostosis Using Posterior Vault Distraction Osteogenesis. Issue 5 (May 2016) - Swanson, Jordan W.; Samra, Fares; Bauder, Andrew; Mitchell, Brianne T.; Taylor, Jesse A.; Bartlett, Scott P.
Abstract : Background: The authors hypothesize that early posterior vault distraction osteogenesis safely confers considerable cranial vault remodeling, sufficient to enable fronto-orbital advancement to be delayed to a later age, with improved outcomes. Methods: The authors conducted a retrospective cohort study of children with syndromic craniosynostosis treated before (2003 to 2008) or after (2009 to 2014) implementation of posterior vault distraction osteogenesis. Results: Sixty children with syndromic craniosynostosis presented during the study period. Forty met inclusion criteria with care continuity and complete records: 22 before and 18 after implementation of posterior vault distraction osteogenesis. Only 11 patients (61 percent) who underwent initial posterior vault distraction osteogenesis required frontal advancement, at a mean follow-up of 4.0 years of age, compared with 22 patients (100 percent) before implementation of posterior vault distraction osteogenesis. Kaplan-Meier survival analysis indicated significant delay of first fronto-orbital advancement in the posterior vault distraction osteogenesis cohort compared with the pre–posterior vault distraction osteogenesis cohort ( p = 0.011). Comparing treatment in the first 5 years of life among posterior vault distraction osteogenesis versus non–posterior vault distraction osteogenesis subcohorts of patients older than 5 years, there were significantly fewer fronto-orbital advancements performed (0.6 versus 1.5 per patient; p = 0.023). Conclusion: Using early posterior vault distraction osteogenesis for patients with syndromic craniosynostosis significantly reduces the average number of fronto-orbital advancement procedures in the first 5 years of life, delays initial fronto-orbital advancement, and is likely to reduce the total number of major craniofacial procedures. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.